2021
DOI: 10.3233/wor-205305
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of healthcare professionals’ perceptions and attitudes towards the COVID-19 pandemic in Turkey

Abstract: BACKGROUND: Determining the healthcare professionals’ perceptions and attitudes towards the COVID-19 pandemic will contribute to managing and struggling their efforts against COVID-19. OBJECTIVE: This study aimed to determine the perceptions and attitudes of healthcare professionals who are at the forefront in the fight against this pandemic. METHODS: In the study, the survey technique used as the data collection method and 216 participants agreed to participate. The questionnaire consisted of three sections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Healthcare professionals generally had positive views about the COVID-19 pandemic. This is in line with Bhagavathula et al [11] who reported positive perceptions on COVID-19 amongst healthcare workers in Iran and in contrast to a study by Turktemiz et al [12] who reported negative perceptions about COVID-19 amongst the study sample.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Healthcare professionals generally had positive views about the COVID-19 pandemic. This is in line with Bhagavathula et al [11] who reported positive perceptions on COVID-19 amongst healthcare workers in Iran and in contrast to a study by Turktemiz et al [12] who reported negative perceptions about COVID-19 amongst the study sample.…”
Section: Discussionsupporting
confidence: 91%
“…This shows positive views towards understanding that the disease can affect anyone, therefore, precautions remain paramount to prevent infection. This is in line with a study by Turktemiz et al [12] who reported that healthcare professionals considered that they would be infected by COVID-19. Wang et al [13] reported that it was a normal consequence that health care professionals believed they would be infected as they were in contact with infected patients.…”
Section: Nyangu M Ramathebanesupporting
confidence: 93%
“…Because nurses have been at the forefront of the struggle against this infectious disease, they have faced a higher risk of infection compared to the general population [7]. Moreover, the insufficient level of knowledge of healthcare professionals about COVID-19, misperceptions, and attitudes towards COVID-19 in the early period may also have caused delayed diagnoses, failure to effectively control the infection, and the spread of the disease (8). Additionally, the rapid increase in cases and deaths, as well as uncertainties about treatment and vaccination complicated efforts to prevent the spread of the disease initially and increased the anxiety of nurses due to workplace risks [3,4,7].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…This fear often facilitates the development of anxiety, insomnia, depression, and disappointment [9]. A systematic review and meta-analysis of the prevalence of depression, anxiety, and stress during the pandemic concluded that almost one-third of nurses had developed depression, anxiety, and stress [8,9]. As of 2020, there were 198,465 nurses working across Turkey's 81 provinces [14].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation